3DOM Cerium Doped LaCoO3 Bifunctional Electrocatalysts for the Oxygen Evolution and Reduction Reactions. Issue 3 (28th December 2021) - Boonlha, Sukit; Chakthranont, Pongkarn; Kityakarn, Sutasinee
Abstract: A bifunctional oxygen evolution reaction and oxygen reduction reaction (OER/ORR) electrocatalyst, macroporous cerium‐doped LaCoO3, was designed based on a dual strategy that included (1) constructing a three‐dimensionally ordered macroporous (3DOM) structure to increase the electrochemical surface area and (2) varying amount of cerium substitution from 0.02 to 0.15 mole fraction of the A site to alter the intrinsic activity of LaCoO3 . The catalytic activity of 3DOM La0.95 Ce0.05 CoO3 (3DOM LCCO‐0.05) is significantly improved over that of the unmodified LaCoO3, with the OER overpotential to reach 10 mA cm −2 lowered by 190 mV, the ORR limiting current density doubled, and the OER‐ORR potential gap reduced by 220 mV to 1.07 V. This enhanced activity is attributed to the increased electrochemical surface area and specific activity, as evidenced by the greater double‐layer capacitances and the lower charge transfer resistances determined by electrochemical impedance spectroscopy (EIS). Furthermore, X‐ray diffraction (XRD) and X‐ray photospectroscopy (XPS) results reveal that these enhanced OER/ORR activities are possibly related to the transformation of the cobalt(III) spin state from low to intermediate or high‐spin, and the increasing amount of surface oxygen species and oxygen vacancies. Abstract : Bifunctional oxygen electrocatalyst : Three‐dimensionally ordered macroporous (3DOM) Ce‐doped LaCoO3 exhibits significantly enhanced bifunctional OER/ORR activity over LaCoO3 . The 3DOM structure increases the electrochemical surface area, while the optimal amount of cerium further improves the specific activity by increasing the spin state transitions of Co 3+ ion and the number of adsorbed oxygen species, as revealed by XRD and XPS.